Enhancing EFL Instruction in Special Needs Education: Integrating Multimodal Digital Tools and Deep Learning Strategies - Prystiananta, Nostalgianti Citra; Noviyanti, Ade Irma (VELES Voices of English Language Education Society, 2025)
Special Needs Education (SNE) faces persistent challenges, particularly in teaching English as a Foreign Language (EFL) to students with disabilities. Limited teacher preparedness, insufficient professional development, and underutilized digital resources contribute to these difficulties, calling for more inclusive instructional approaches. This study explores how multimodal digital tools and deep learning pedagogical strategies—emphasizing higher-order thinking and critical reflection—can support teacher competence and instructional quality in EFL classrooms within the SNE context. Employing a mixed-methods design, the study involved 50 teachers from integrated schools for students with special needs in Indonesia, spanning primary to high school levels. These teachers participated in a professional development program focused on designing interactive digital books using the Book Creator platform. The findings of this study reveal that integrating multimodal digital tools contributed to increased engagement, accessibility, and differentiated instruction for students. At the same time, deep learning strategies encouraged more reflective and adaptive teaching practices. Nevertheless, challenges such as limited access to technology and the need for ongoing training continue to affect implementation. The study recommends sustained institutional support and targeted professional development to promote more inclusive and responsive EFL instruction in special education settings.